The ComSoc guide to managing telecommunications projects Celia Desmond. - Desmond, Celia (Wiley ; IEEE Press, 2010)
"This pocket guide provides an overview of the telecommunications environment as it has evolved over the past few years, illustrating the need for project management, the significance of project success to the companies, and the application of key project management processes within the telecom environment. Topics covered include: scope management, time management, cost management, procurement management, risk management, communications, quality, human resources, and Integration. It offers professionals a brief and accessible guide to managing telecommunication projects in the 21st century"-- Provided by publisher.
Keywords: Telecommunication -- Management.; Project management.